2008
DOI: 10.1007/s00204-008-0345-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium and lead: molecular mechanisms of brain toxicity

Abstract: The fact that aluminium (Al) and lead (Pb) are both toxic metals to living organisms, including human beings, was discovered a long time ago. Even when Al and Pb can reach and accumulate in almost every organ in the human body, the central nervous system is a particular target of the deleterious effects of both metals. Select human population can be at risk of Al neurotoxicity, and Al is proposed to be involved in the etiology of neurodegenerative diseases. Pb is a widespread environmental hazard, and the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
250
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(264 citation statements)
references
References 133 publications
3
250
0
11
Order By: Relevance
“…Among the relevant factors, metal ions could aggravate the course of AD [14] . Al ion exposure could cause conformational change of Aβ [15,16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the relevant factors, metal ions could aggravate the course of AD [14] . Al ion exposure could cause conformational change of Aβ [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the dried root of Radix Polygonum Multiflorum (16 kg) was roughly grounded and refluxed with ethanol twice (each lasted for 1 h). The ethanol extracts were filtered and lyophilized to form powder TSG [14] .…”
Section: Drug Preparationmentioning
confidence: 99%
“…Aluminum is one of the most abundant metals in the earth's crust (Verstraeten et al, 2008), and is found in its ionic form in animal and plant tissues while, in nature it is found in combination with other elements such as oxygen, sulfate, chloride and other elements because of it is high reactivity (ATSDR, 2007). Humans are exposed to aluminum compounds from various sources as aluminum found in many food additives, toothpaste, medicines (such as aspirin), cheese, tea, cosmetics, drinking water, various household cookware and storage utensils; in addition aluminum is used to construct roofing and for many other industrial activities (Proudfoot, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pb exposure also causes generation of reactive oxygen species (ROS), resulting in impairment of neurotransmission in animals (Verstraeten et al, 2008). The exposure of fish and wildlife in e-waste recycling areas to harmful toxicants, such as Pb and BDE-209, is a critical issue, and concomitant exposure to multiple toxicants may have exacerbated detrimental effects.…”
Section: Introductionmentioning
confidence: 99%